2016
DOI: 10.1371/journal.pcbi.1005215
|View full text |Cite
|
Sign up to set email alerts
|

Combined Changes in Chloride Regulation and Neuronal Excitability Enable Primary Afferent Depolarization to Elicit Spiking without Compromising its Inhibitory Effects

Abstract: The central terminals of primary afferent fibers experience depolarization upon activation of GABAA receptors (GABAAR) because their intracellular chloride concentration is maintained above electrochemical equilibrium. Primary afferent depolarization (PAD) normally mediates inhibition via sodium channel inactivation and shunting but can evoke spikes under certain conditions. Antidromic (centrifugal) conduction of these spikes may contribute to neurogenic inflammation while orthodromic (centripetal) conduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Notably, PAD was so far only described for spinal and not meningeal afferents which, however, does not exclude the possibility of its generation in this part of the nociceptive system. It has been shown that the distribution of intracellular chloride (high in sensory neurons) enables the PAD to elicit spiking activity without compromising the inhibitory effect of GABA on primary afferents (Takkala et al, 2016 ). However, we used the hemiskull preparation, which contained trigeminal ganglia but was isolated from the brainstem/spinal cord.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, PAD was so far only described for spinal and not meningeal afferents which, however, does not exclude the possibility of its generation in this part of the nociceptive system. It has been shown that the distribution of intracellular chloride (high in sensory neurons) enables the PAD to elicit spiking activity without compromising the inhibitory effect of GABA on primary afferents (Takkala et al, 2016 ). However, we used the hemiskull preparation, which contained trigeminal ganglia but was isolated from the brainstem/spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been shown that the antidromic stimulation increased the effectiveness of orthodromic activity via sensitization of C-fibers (Gong and Lin, 2019 ). Moreover, during inflammation, GABAergic PAD (proposed as generator of antidromic activity) is increased (Willis, 1999 ; Lin et al, 2007 ), leading to enhanced orthodromic spiking (Takkala et al, 2016 ). These non-canonical GABAergic excitatory mechanism along with increased intra-ganglion crosstalk between neurons and glia could result in migraine-related peripheral effects in the meninges such as enhanced CGRP release, vasodilation, mast cell degranulation, and associated local sterile inflammation (Messlinger, 2009 ; Della Pietra et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…) and GABA A receptor signalling (Takkala et al . ). Beyond testing the effects of known molecular changes, our group has used dynamic clamp to reproduce known changes in cellular excitability in order to explore the underlying molecular changes in a more general way, including how such changes may combine to affect excitability (Ratté et al .…”
Section: Discussionmentioning
confidence: 97%
“…In physiological conditions, PAD exerts an inhibitory effect on glutamate release, through several possible mechanisms. PAF depolarization can lead to the inactivation of voltage-dependent Na + and Ca + channels, impairing the propagation of action potentials along PAFs and decreasing the calcium influx into the terminals [ 18 , 19 , 20 , 21 , 22 ]. The opening of GABA A channels could also exert a shunting effect on action potential propagation by decreasing membrane resistivity, as shown by experimental evidence and mathematical simulations [ 23 , 24 , 25 , 26 ].…”
Section: Gabaergic Inhibition On Primary Afferent Fibersmentioning
confidence: 99%
“…Following nerve injury, PAD amplitude is generally reduced and presynaptic inhibition is diminished [ 70 , 71 ]. Several factors seem to contribute to PAD modifications in neuropathic pain: (1) decrease of GABA synthesis, due to the reduced expression of the GABA synthetizing enzyme GAD65 in dorsal horn inhibitory interneurons [ 8 , 80 ]; (2) increase of NKCC1 expression and activity, causing a depolarizing shift of E Cl [ 22 , 81 , 82 ]; and (3) reduction of GABA A conductance and downregulation of γ2, α2, and α1 subunits on DRG neurons, observed after nerve ligation, chronic constriction, and crush nerve injury [ 10 , 83 , 84 , 85 , 86 ]. Consistently, the selective downregulation of the α2 subunit in DRGs worsens thermal and mechanical hypersensitivity in crush-injured animals and induces pain hypersensitivity in sham animals, while upregulation of endogenous GABA alleviates neuropathic pain [ 86 ].…”
Section: Modifications Of Presynaptic Inhibition In Chronic Painmentioning
confidence: 99%